PENERAPAN PSAK 73 TERHADAP LAPORAN KEUANGAN DALAM MENINGKATKAN RELEVANSI LAPORAN KEUANGAN - Aprilia, Visca Angga; Anggraini, Ninik; Yani, Ahmad (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
Company required to report its financial statements in a relevant manner, there is provision of PSAK 73 Leases. PSAK 73 Leases determines the recognition, measurement, presentation and disclosure of leases for companies in order to increase the relevance value. A high level of relevance makes the policy taken appropriate company. This research is descriptive research with a quantitative approach. Types of research data are quantitative and qualitative. Research data techniques are documentation and interviews. The research variable is application of PSAK No. 73 concerning leases, financial statements and the relevance of financial statements. The results of this study are that the company records leased assets only with an operating lease model, reflecting only 1 year lease. Implementation of PSAK No. 73 concerning Lease on PT. Anugerah Beton Indonesia made the assets section of the financial position report increase, so that the impact of implementing PSAK 73 made the company's total assets, total liabilities and equity increase. This increase shows the assets and liabilities owned by the company in the coming year, so that the application of PSAK No. 73 on Leases is able to increase the relevance of the financial position report of PT. Indonesian Concrete Award in 2021.